Electrolyte, battery and electric equipment

By using electrolyte containing sulfonamide and cyclic sulfur-containing additives in lithium-ion batteries to form a high thermal stability SEI film, the problem of insufficient electrolyte stability in lithium-ion batteries in high temperature environments is solved, and the circulation and safety performance of the battery is significantly improved.

CN119627226APending Publication Date: 2025-03-14XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411943370.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have insufficient stability in electrolytes in high-temperature environments, resulting in low safety performance and poor circulation and high-temperature storage performance.

Method used

Using an electrolyte containing sulfonamide additives and cyclic sulfur-containing additives, the sulfonamide additives form lithium sulfonate through reduction and decomposition to form SEI films. Under the synergistic action, the cyclic sulfur-containing additives form a high degree of sulfur-containing substance and improve the thermal stability of the SEI film.

Benefits of technology

It significantly improves the circulation, safety performance and high-temperature storage performance of lithium-ion batteries in normal temperature and high temperature environments, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627226A_ABST
    Figure CN119627226A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte, a battery and electric equipment. The electrolyte comprises a first additive and a second additive, the first additive is a sulfonamide additive, and the first additive comprises a cyclic conjugated group; the second additive is an annular sulfur-containing additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art

[0002] With the continuous development of lithium-ion battery technology, lithium-ion batteries are required to have lower life attenuation and longer service life. At the same time, higher requirements are placed on the stability of lithium-ion battery electrolytes in high temperature environments so that lithium-ion batteries have higher safety performance. Therefore, there is an urgent need for an electrolyte with high thermal stability to improve the safety performance of lithium-ion batteries. Summary of the invention

[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device, wherein the electrolyte has high thermal stability.

[0004] The present application provides an electrolyte, which includes: a first additive and a second additive, wherein the first additive is a sulfonamide additive, and the first additive includes a cyclic conjugated group; and the second additive is a cyclic sulfur-containing additive.

[0005] Furthermore, the structural formula of the first additive is: Among them, R1 includes at least one of hydrogen, methyl, trifluoromethyl, and halogen, R2 is the cyclic conjugated group, and the cyclic conjugated group includes at least one of phenyl, pyridyl, pyrazinyl, thienyl, and pyrrolyl, R3 includes at least one of hydrogen, phenyl, methyl, and ethyl, and R4 includes at least one of hydrogen, phenyl, methyl, and ethyl.

[0006] Furthermore, the first additive is selected from and At least one of .

[0007] Furthermore, in the electrolyte, the mass fraction a of the first additive is in the range of 0.01%≤a≤1%.

[0008] Furthermore, the second additive is selected from at least one of vinyl sulfate, 1,3-propylene sultone and methylene methane disulfonate.

[0009] Furthermore, in the electrolyte, the mass fraction b of the second additive is in the range of 0.05%≤b≤2%.

[0010] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 0.1≤a / b≤1.

[0011] Furthermore, the electrolyte satisfies the relationship: 0.5≤a / b≤1.

[0012] The present application provides a battery, which includes: an electrode assembly and an electrolyte provided by the present application, wherein the electrode assembly includes a positive electrode plate, a separator and a negative electrode plate, and the positive electrode plate, the separator and the negative electrode plate are stacked; the electrolyte is used to infiltrate at least a portion of the electrode assembly.

[0013] The present application provides an electrical device, which includes: a device body and a battery provided in the present application, wherein the battery supplies power to the device body.

[0014] In the present application, the electrolyte includes a first additive, which is a sulfonamide additive. In other words, the first additive includes an aminosulfonyl structure to effectively reduce the LUMO energy level of the first additive, so that the first additive is easy to be reduced. When the first additive is applied to the electrolyte, the first additive preferentially undergoes a reduction decomposition reaction compared to other components in the electrolyte to generate aminosulfonate ions. The aminosulfonate ions combine with lithium ions in the electrolyte to form aminosulfonate lithium and adhere to the surface of the negative electrode to form a SEI (Solid Electrolyte Interphase) film. Lithium aminosulfonate has good electrical insulation and can improve the chemical stability of the SEI film to reduce the consumption of lithium ions in the SEI film and repair process. In addition, the first additive also includes a conjugated group, and the product of the reduction decomposition reaction of the first additive also includes a free radical containing a conjugated group. This free radical containing a conjugated group has a strong nucleophilicity. When the electrolyte also includes a second additive and the second additive is a cyclic sulfur-containing additive, the free radical containing a conjugated group can effectively promote the ring opening of the second additive, and make the second additive form a sulfur-containing substance with a higher degree of polymerization. The first additive and the second additive have a synergistic effect. On the one hand, under the action of the free radical containing a conjugated group and having a strong nucleophilicity generated by the decomposition of the first additive, the polymerization degree of the polymer formed by the second additive is higher, so that the solubility of the SEI film in the electrolyte is lower, which is conducive to reducing the dissolution of the SEI film during high-temperature cycling, thereby slowing down the consumption of lithium ions in the electrolyte under high-temperature cycling. On the second hand, the polymerization degree of the polymer formed by the second additive is higher, so that the sulfur-containing components in the SEI film are more, and the stability of the SEI film during high-temperature cycling can be further improved, so that the electrolyte also has good stability under high-temperature cycling. When the electrolyte is applied to a battery, the battery has good cycle performance and safety performance under normal temperature and high temperature environments, and has good high temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 A partial cross-sectional structural schematic diagram of a battery according to an embodiment of the present application;

[0017] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;

[0018] Figure 3 This is a circuit block diagram of an electrical device according to an embodiment of the present application.

[0019] Description of reference numerals:

[0020] 100 - electrolyte, 200 - battery, 210 - electrode assembly, 211 - positive electrode plate, 212 - diaphragm, 213 - negative electrode plate, 300 - electrical equipment, 310 - equipment body. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0023] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0024] With the continuous development of lithium-ion battery technology, lithium-ion batteries are required to have lower life attenuation and longer service life. At the same time, higher requirements are placed on the stability of the electrolyte of lithium-ion batteries in high temperature environments, so that lithium-ion batteries have higher safety performance.

[0025] At present, most companies in the energy storage field use lithium iron phosphate as the main positive electrode active material. Lithium iron phosphate has the advantages of not easy to release oxygen and good electrochemical and thermal stability, but it also has the disadvantage of low energy density. In order to improve the energy density of lithium iron phosphate energy storage cells and reduce production costs, higher electrode coatings and higher cold pressing compaction densities are used. At the same time, the capacity of single cells is getting larger and larger. On the basis of the same active material capacity, the amount of current collector and electrolyte used is reduced. While these strategies bring high energy density and reduce costs, the stability of the cells under high temperature conditions is becoming increasingly prominent. In large-capacity cells, the cells generate high heat and have poor heat dissipation. During operation, heat accumulates, and the electrolyte is easy to decompose and evaporate, resulting in increased pressure inside the cell, and may even cause the cell to catch fire or explode. Therefore, there is an urgent need for an electrolyte with high thermal stability to improve the cycle performance, high-temperature storage performance and safety performance of lithium-ion batteries.

[0026] It can be understood that a higher electrode coating means that the positive electrode active material in the electrode has a higher coating amount, and a higher cold pressing compaction means that the positive electrode has a higher compaction density.

[0027] See also Figure 1 The present application provides a battery 200, which includes: an electrode assembly 210 and an electrolyte 100 provided in the present application, wherein the electrode assembly 210 includes a positive electrode sheet 211, a separator 212 and a negative electrode sheet 213, and the positive electrode sheet 211, the separator 212 and the negative electrode sheet 213 are stacked; the electrolyte 100 is used to infiltrate at least a portion of the electrode assembly 210.

[0028] Optionally, in some embodiments, the battery 200 is a lithium-ion battery.

[0029] It can be understood that the electrolyte 100 is used to infiltrate the electrode assembly 210 to achieve the transmission of active ions in the battery 200 between the positive electrode sheet 211 and the negative electrode sheet 213. When the battery 200 is a lithium-ion battery, the active ions are lithium ions.

[0030] In the present embodiment, the battery 200 includes the electrolyte 100 provided in the embodiment of the present application, and the electrolyte 100 includes a first additive and a second additive. The first additive preferentially undergoes a reduction decomposition reaction compared to other components in the electrolyte 100 to generate aminosulfonate ions, and the aminosulfonate ions combine with the lithium ions in the electrolyte 100 to form aminosulfonate lithium and adhere to the surface of the negative electrode plate 213 to form a SEI (Solid Electrolyte Interphase) film. Lithium aminosulfonate has good electrical insulation and can improve the chemical stability of the SEI film to reduce the consumption of lithium ions in the SEI film and repair process. In addition, the first additive also includes a conjugated group, and the product of the reduction decomposition reaction of the first additive also includes a free radical containing a conjugated group. This free radical containing a conjugated group has a strong nucleophilicity. The free radical containing a conjugated group can effectively promote the ring opening of the second additive and allow the second additive to form a sulfur-containing substance with a higher degree of polymerization. The first additive and the second additive have a synergistic effect, so that the degree of polymerization of the polymer formed by the second additive is higher, so that the solubility of the SEI film in the electrolyte 100 is lower, which is conducive to reducing the dissolution of the SEI film during high-temperature cycling, thereby slowing down the consumption of lithium ions in the electrolyte 100 under high-temperature cycling. In addition, the higher the degree of polymerization of the polymer formed by the second additive, the more sulfur-containing components in the SEI film, and the further improvement of the stability of the SEI film during high-temperature cycling, so that the electrolyte 100 also has good stability under high-temperature cycling, and finally the battery 200 has good cycle performance and safety performance in both normal temperature and high-temperature environments, and has good high-temperature storage performance.

[0031] It can be understood that in the terminology of this application, "high temperature" is relative to "normal temperature", normal temperature generally refers to room temperature, such as between 10° C. and 30° C., and high temperature generally refers to more than 30° C. This is only an example of high temperature and normal temperature, and should not be understood as a limitation on high temperature and normal temperature.

[0032] It can be understood that, in the terminology of the present application, “high temperature storage performance” can represent the stability of the battery 200 when stored in a high temperature environment.

[0033] Understandably, Figure 1 The battery 200 shown is a cylindrical battery, and the battery 200 may also be a square battery. Figure 1 The embodiment merely provides an illustration of the battery 200 and should not be construed as limiting the shape of the battery 200 .

[0034] Optionally, in some embodiments, the diaphragm 212 is a polypropylene diaphragm, a polyethylene diaphragm or a coated diaphragm.

[0035] Optionally, the positive electrode plate 211 includes a stacked positive electrode collector layer and a positive electrode material layer, the positive electrode material layer is arranged on at least one surface of the positive electrode collector layer, and the positive electrode material layer includes a positive electrode active material, a positive electrode binder, a positive electrode conductor and a positive electrode thickener.

[0036] Optionally, the positive electrode current collector layer is selected from aluminum foil.

[0037] Optionally, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene or styrene butadiene rubber (SBR). In the positive electrode material layer, the mass fraction of the positive electrode binder ranges from 2% to 4%.

[0038] Optionally, the negative electrode plate 213 includes a stacked negative electrode current collector layer and a negative electrode material layer, the negative electrode material layer is arranged on at least one surface of the negative electrode current collector layer, and the negative electrode material layer includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent and a negative electrode thickener.

[0039] Optionally, the negative electrode current collector layer is selected from copper foil.

[0040] Optionally, the negative electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene or styrene butadiene rubber (SBR). In the negative electrode material layer, the mass fraction of the negative electrode binder ranges from 2% to 4%.

[0041] The present application provides an electrolyte 100, which includes: a first additive and a second additive, wherein the first additive is a sulfonamide additive, and the first additive includes a cyclic conjugated group; and the second additive is a cyclic sulfur-containing additive.

[0042] It can be understood that the first additive and the second additive are film-forming additives.

[0043] In this embodiment, the electrolyte 100 includes a first additive, which is a sulfonamide additive. In other words, the first additive includes an aminosulfonyl structure to effectively reduce the LUMO energy level of the first additive, so that the first additive is easy to be reduced. When the first additive is applied to the electrolyte 100, the first additive preferentially undergoes a reduction decomposition reaction compared to other components in the electrolyte 100 to generate aminosulfonate ions. The aminosulfonate ions combine with the lithium ions in the electrolyte 100 to form aminosulfonate lithium and adhere to the surface of the negative electrode plate 213 to form a SEI (Solid Electrolyte Interphase) film. Lithium aminosulfonate has good electrical insulation and can improve the chemical stability of the SEI film to reduce the consumption of lithium ions in the SEI film and repair process. In addition, the first additive also includes a conjugated group, and the product of the reduction decomposition reaction of the first additive also includes a free radical containing a conjugated group. This free radical containing a conjugated group has a strong nucleophilicity. When the electrolyte 100 also includes a second additive and the second additive is a cyclic sulfur-containing additive, the free radical containing a conjugated group can effectively promote the ring opening of the second additive, and make the second additive form a sulfur-containing substance with a higher degree of polymerization. The first additive and the second additive have a synergistic effect. On the one hand, under the action of the free radical containing a conjugated group and having a strong nucleophilicity generated by the decomposition of the first additive, the polymerization degree of the polymer formed by the second additive is higher, so that the solubility of the SEI film in the electrolyte 100 is lower, which is conducive to reducing the dissolution of the SEI film during high-temperature cycling, thereby slowing down the consumption of lithium ions in the electrolyte 100 under high-temperature cycling. On the other hand, the higher the degree of polymerization of the polymer formed by the second additive, the more sulfur-containing components in the SEI film, and the further improvement of the stability of the SEI film during high-temperature cycling, so that the electrolyte 100 also has good stability under high-temperature cycling. When the electrolyte 100 is applied to the battery 200, the battery 200 has good cycle performance and safety performance under normal temperature and high temperature environment, and has good high temperature storage performance.

[0044] It is understood that in the terminology of this application, "LUMO (Lowest Unoccupied Molecular Orbital) energy level" refers to the lowest energy molecular orbital in a molecule that is not occupied by electrons. Lowering the LUMO energy level can make the substance more easily accept electrons, thereby showing better reduction reaction ability in electrochemical reactions.

[0045] Optionally, the reducing property of the first additive is greater than that of the second additive. In other words, when the first additive and the second additive are applied to the electrolyte 100, the first additive undergoes a reduction reaction preferentially compared to the second additive, so that the product generated by the reduction reaction of the first additive preferentially forms a film.

[0046] In some embodiments, the first additive has a structural formula of: Among them, R1 includes at least one of hydrogen, methyl, trifluoromethyl, and halogen, R2 is the cyclic conjugated group, and the cyclic conjugated group includes at least one of phenyl, pyridyl, pyrazinyl, thienyl, and pyrrolyl, R3 includes at least one of hydrogen, phenyl, methyl, and ethyl, and R4 includes at least one of hydrogen, phenyl, methyl, and ethyl.

[0047] It can be understood that, in the terms of the present application, "at least one" means one or more, and "plurality" means greater than or equal to two, which can be but is not limited to two, three, etc.

[0048] In this embodiment, the structural formula of the first additive is On the one hand, the structural formula includes an aminosulfonyl structure, so that the first additive is superior to other components in the electrolyte 100, such as the second additive, in the reduction reaction, and generates lithium aminosulfonate with electronic insulation, so that the SEI film has better stability. On the other hand, R1 is selected from at least one of hydrogen, methyl, trifluoromethyl, and halogen, and R2 is selected from at least one of phenyl, pyridyl, pyrazinyl, thienyl, and pyrrolyl, and R1 and R2 cooperate with each other to make the first additive have a strong nucleophilicity. When the first additive undergoes a decomposition reaction, the decomposition product formed includes a free radical containing R1 and R2, which has a strong nucleophilicity and is more likely to attack the second additive, so as to promote the ring opening of the second additive and make the polymer formed by the second additive have a higher degree of polymerization, so that the solubility of the SEI film in the electrolyte 100 is lower, which is conducive to reducing the dissolution of the SEI film during high-temperature cycling, thereby slowing down the consumption of lithium ions in the electrolyte 100 under high-temperature cycling. On the other hand, R3 includes at least one of hydrogen, phenyl, methyl, and ethyl, and R4 includes at least one of hydrogen, phenyl, methyl, and ethyl. The decomposition product of the reduction reaction of the first additive, aminosulfonate ions, includes R3 and R4. Hydrogen, phenyl, methyl, and ethyl have good binding properties with lithium ions, so that the formed aminosulfonate lithium structure has good lithium ion conductivity, so that the SEI film formed by the first additive and the second additive has good ion conductivity, which is convenient for reducing the internal resistance of the battery 200, so that the battery 200 has good cycle performance, and has good cycle stability both at normal temperature and high temperature. The battery 200 also has good high temperature storage performance.

[0049] In some embodiments, the first additive is selected from and At least one of .

[0050] In this embodiment, the first additive is selected from and At least one of the above, so that the first additive can be reduced before the second additive to generate lithium sulfamate with electrical insulation, and lithium sulfamate has a higher ionic conductivity, so that the SEI film not only has better chemical stability, but also reduces the impedance of lithium ions passing through the SEI film; furthermore, the first additive can also attack the second additive and promote the ring opening of the second additive, so that the polymer formed by the second additive has a higher degree of polymerization, so that the SEI film has better thermal stability. When the first additive provided in this embodiment is applied to the electrolyte 100, the electrolyte 100 has better cycle performance in both normal temperature environment and high temperature environment, and improves the thermal stability of the electrolyte 100, thereby improving the cycle performance, safety performance and high temperature storage performance of the battery 200 when the electrolyte 100 is applied to the battery 200.

[0051] In some embodiments, in the electrolyte 100 , the mass fraction a of the first additive is in the range of 0.01%≤a≤1%.

[0052] Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1%, etc.

[0053] In the electrolyte 100 provided in the present embodiment, after the first additive undergoes a reduction decomposition reaction, the decomposition product of the first additive includes a free radical containing a conjugated group. After the free radical containing a conjugated group promotes the ring opening of the second additive, multiple second additives react with each other to form multiple repeating units. In other words, after the free radical containing a conjugated group promotes the ring opening of a small part of the multiple second additives, the remaining second additives that have not been ring-opened can be ring-opened under the action of the second additive that has been ring-opened, and the amount of the first additive is trace. When the mass fraction a of the first additive satisfies the range of 0.01%≤a≤1%, the mass fraction a of the first additive is within a reasonable range. On the one hand, the free radical containing a conjugated group formed by the decomposition of the first additive can effectively promote the ring opening of the second additive, so that the second additive forms a polymer with a high degree of polymerization on the surface of the negative electrode plate 213 and forms an SEI film, and the polymer formed by the second additive contains sulfur, so that the SEI film has good thermal stability, thereby making the electrolyte 100 have good thermal stability. On the other hand, the number of aminosulfonate ions formed by the decomposition of the first additive is also within a reasonable range, and can be combined with lithium ions in the electrolyte 100 and form an SEI film with electronic insulation and high ion conductivity on the surface of the negative electrode plate 213, so as to form a film first, reduce the transmission impedance of lithium ions in the electrolyte 100, so that the battery 200 has better cycle performance when the electrolyte 100 is applied to the battery 200. When the mass fraction of the first additive is too large, the free radicals containing conjugated groups decomposed by the first additive are too many, and only a small part of the free radicals containing conjugated groups are used to promote the ring-opening polymerization of the second additive, and the remaining free radicals containing conjugated groups are free in the electrolyte 100, which will increase the impedance of the electrolyte 100, thereby reducing the cycle performance of the battery 200. When the mass fraction of the first additive is too small, the mass proportion of the first additive in the electrolyte 100 is too small, so that the first additive cannot effectively play a role in promoting the ring opening of the second additive, the degree of polymerization of the polymer formed by the second additive is low, and the sulfur content in the formed SEI film is reduced, thereby making the thermal stability of the SEI film poor and the thermal stability of the electrolyte 100 poor.

[0054] Preferably, in the electrolyte 100, the mass fraction a of the first additive is in the range of 0.1%≤a≤0.5%. Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, etc.

[0055] In some embodiments, the second additive is selected from at least one of diethylene sulfate (DTD), 1,3-propene sultone (PST), and methylene methane disulfonate (MMDS).

[0056] It can be understood that the cyclic sulfur-containing additive includes cyclic sulfates and cyclic sulfonates, vinyl sulfate is one of the cyclic sulfates, and 1,3-propylene sultone and methylene methane disulfonate are one of the cyclic sulfonates.

[0057] In this embodiment, when the second additive is selected from at least one of vinyl sulfate, 1,3-propylene sultone and methylene disulfonate, the second additive is ring-opened under the promotion of the first additive, and the polymer formed by the second additive and the first additive has a high degree of polymerization, so that the SEI film is not easily dissolved during high-temperature cycling, which can reduce the consumption of active lithium in the electrolyte 100, thereby improving the thermal stability of the electrolyte 100.

[0058] It can be understood that the structural formula of the first additive is The structural formula of the second additive is

[0059] For example, the reaction formula for the reduction decomposition reaction of the first additive is:

[0060] The reaction formula of the free radical containing conjugated groups generated by the first additive promoting the ring opening of the second additive is as follows:

[0061]

[0062] In some embodiments, in the electrolyte 100 , the mass fraction b of the second additive is in the range of 0.05%≤b≤2%.

[0063] Specifically, the mass fraction b of the second additive can be, but is not limited to, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% and 2%, etc.

[0064] In the electrolyte 100 provided in this embodiment, when the mass fraction b of the second additive satisfies the range of 0.05%≤b≤2%, the mass fraction of the second additive is within a reasonable range. On the one hand, the second additive generates a polymer with a high degree of polymerization under the promotion of the first additive to form an SEI film attached to the surface of the negative electrode plate 213, and the SEI film is not easily dissolved by the electrolyte 100 under high-temperature cycles. The SEI film contains more sulfur, which also makes the SEI film have a higher thermal stability, so that the electrolyte 100 has better thermal stability. When the electrolyte 100 is applied to the battery 200, the battery 200 has better high-temperature performance and safety performance. On the other hand, the mass fraction of the second additive is not too large or too small to increase the internal resistance of the battery 200, so that when the electrolyte 100 is applied to the battery 200, the battery 200 has better cycle performance. When the mass fraction of the second additive is too large, under the action of the first additive, the second additive opens the ring faster and the polymerization degree of the formed polymer is too high, so that the SEI film may be too thick, increasing the transmission path and impedance of lithium ions in the battery 200 passing through the SEI film, thereby reducing the cycle performance of the battery 200. When the mass fraction of the second additive is too small, even if the first additive can promote the opening of the second additive, the mass content of the second additive in the electrolyte 100 is still too small, so that the polymerization degree of the polymer formed by the first additive and the second additive is too low, and the first additive and the second additive are combined, and it is difficult to form a complete SEI film on the surface of the negative electrode plate 213, which increases the impedance of lithium ions in the battery 200 transmitted between the electrolyte 100 and the negative electrode plate 213, thereby reducing the cycle performance of the battery 200.

[0065] Preferably, the mass fraction b of the second additive is in the range of 0.5%≤b≤1.5%. Specifically, the mass fraction b of the second additive may be, but is not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0066] In some embodiments, in the electrolyte 100 , the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte 100 satisfies the relationship: 0.1≤a / b≤1.

[0067] Specifically, the value of a / b can be, but is not limited to, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.8, 0.9, 0.95, 0.98 and 1, etc.

[0068] It can be understood that, in the electrolyte 100, the mass fraction of the first additive is less than or equal to the mass fraction of the second additive.

[0069] In the electrolyte 100 provided in this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 0.1≤a / b≤1, the mass fraction a of the first additive and the mass fraction b of the second additive are within a reasonable range. On the one hand, the free radicals containing conjugated groups formed by the decomposition of the first additive can effectively promote the ring opening of the second additive, so that the second additive forms a polymer with a high degree of polymerization and forms an SEI film on the surface of the negative electrode plate 213. The SEI film with a high degree of polymerization is not easily dissolved by the electrolyte 100 under high-temperature cycles, and the polymer formed by the second additive contains sulfur, so that the SEI film has good thermal stability, thereby making the electrolyte 100 have good thermal stability. On the other hand, the number of aminosulfonate ions formed by the decomposition of the first additive is also within a reasonable range, and can combine with lithium ions in the electrolyte 100 and form an SEI film with electronic insulation and high ion conductivity on the surface of the negative electrode plate 213, so as to form a film first and reduce the transmission impedance of lithium ions in the electrolyte 100, so that the battery 200 has better cycle performance when the electrolyte 100 is applied to the battery 200. Furthermore, the mass fraction of the second additive is not too large or too small to increase the internal resistance of the battery 200, so that the battery 200 has better cycle performance when the electrolyte 100 is applied to the battery 200. When the value of a / b is too large, the mass fraction of the first additive is too large or the mass fraction of the second additive is too small. If the mass fraction of the first additive is too large, the free radicals containing conjugated groups decomposed by the first additive are too many, and only a small part of the free radicals containing conjugated groups are used to promote the ring-opening polymerization of the second additive. The remaining free radicals containing conjugated groups are free in the electrolyte 100, which will increase the impedance of the electrolyte 100, thereby reducing the cycle performance of the battery 200. If the mass fraction of the second additive is too small, even if the first additive can promote the ring-opening of the second additive, the mass content of the second additive in the electrolyte 100 is still too small, so that the polymerization degree of the polymer formed by the first additive and the second additive is too low. The first additive and the second additive are combined, and it is difficult to form a complete SEI film on the surface of the negative electrode plate 213, which increases the impedance of the lithium ions in the battery 200 transmitted between the electrolyte 100 and the negative electrode plate 213, thereby reducing the cycle performance of the battery 200.When the value of a / b is too small, the mass fraction of the first additive is too small or the mass fraction of the second additive is too large, then even if the first additive can promote the ring opening of the second additive, the degree of polymerization of the polymer formed by the first additive and the second additive is still too low. When the electrolyte 100 is applied to the battery 200 and the battery 200 is in a high-temperature cycle, the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 213 is easily dissolved, thereby increasing the interfacial transmission impedance of lithium ions, and also consuming more lithium ions to repair the SEI film, so that the high-temperature cycle performance and high-temperature storage performance of the battery 200 are poor. When the battery 200 is in a high-temperature working environment and stored at high temperatures, volume expansion and other phenomena may occur, thereby shortening the service life of the battery 200.

[0070] Preferably, in some embodiments, the electrolyte 100 satisfies the relationship: 0.5≤a / b≤1. The ratio of the mass fraction of the first additive to the mass fraction of the second additive in the electrolyte 100 is within a preferred range, the electrolyte 100 has better thermal stability, and when the electrolyte 100 is applied to the battery 200, the battery 200 has better cycle performance both at room temperature and at high temperature, and the battery 200 has better high temperature storage performance.

[0071] Specifically, the value of a / b may be, but is not limited to, 0.5, 0.55, 0.6, 0.65, 0.7, 0.8, 0.9, 0.95, 0.98, and 1.

[0072] Optionally, the electrolyte 100 further includes a solvent, and the solvent is used to dissolve the first additive and the second additive.

[0073] In the electrolyte 100, the mass fraction of the solvent ranges from 60% to 85%. Specifically, the mass fraction of the solvent may be, but is not limited to, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 84%, 85%, etc.

[0074] Optionally, the solvent is selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). In some specific embodiments, the solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), and the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 2:1:2.

[0075] Optionally, the electrolyte 100 further includes a lithium salt, which is dissolved in the electrolyte 100 and is used to provide active lithium ions for the electrolyte 100 .

[0076] Optionally, the lithium salt is selected from LiPF 6 , LiBF 4 , LiFSi, LiTFSi, LiBOB, LiODFP, LiODFB, LiPO 2 F 2 or CF 3 SO 3 At least one of Li.

[0077] The technical solution of this application is further introduced in the following with multiple embodiments:

[0078] Example 1 to Example 14, Comparative Example 1 to Comparative Example 7:

[0079] 1. Preparation of positive electrode sheet 211:

[0080] The positive electrode active material lithium iron phosphate, the positive electrode conductive agent conductive carbon black (SP), and the positive electrode binder polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methylpyrrolidone (NMP) according to a mass ratio of 97:0.7:2.3, and different mass percentages of PVDF are added at the same time, and mixed evenly to obtain a positive electrode slurry with a solid content of 60wt%; the positive electrode slurry is coated on the positive electrode collector layer (aluminum foil), and after drying, cold pressing, slitting, and cutting, a positive electrode material layer is obtained to obtain a positive electrode sheet 211.

[0081] 2. Preparation of negative electrode sheet 213:

[0082] The negative electrode active material artificial graphite, the negative electrode conductive agent conductive carbon black (SP), the negative electrode thickener carboxymethyl cellulose (CMC) and the negative electrode binder styrene butadiene rubber (SBR) are dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is coated on the negative electrode collector layer (aluminum foil), and after drying, cold pressing, slitting and cutting, a negative electrode material layer is obtained to obtain a negative electrode sheet 213.

[0083] 3. Preparation of electrolyte 100:

[0084] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:1:2, and then the dry lithium salt lithium hexafluorophosphate is dissolved in the solvent and stirred until completely dissolved and uniformly dissolved. After adding the first additive and the second additive and mixing evenly, the electrolyte 100 of Examples 1 to 14 and Comparative Examples 1 to 7 is obtained.

[0085] Among them, in the electrolyte 100 of Examples 1 to 14 and Comparative Examples 1 to 7, the mass fraction of lithium salt lithium hexafluorophosphate is 13%, and the type of the first additive, the value of the mass fraction a of the first additive, the type of the second additive and the value of the mass fraction b of the second additive are as shown in Table 1.

[0086] 4. Preparation of diaphragm 212:

[0087] A 16 um polyethylene film is used as the diaphragm 212 .

[0088] 5. Preparation of Battery 200:

[0089] The prepared positive electrode sheet 211, diaphragm 212, and negative electrode sheet 213 are stacked in order so that the diaphragm 212 is located between the positive electrode sheet 211 and the negative electrode sheet 213. A bare battery cell is obtained after winding. After welding the pole ears, the bare battery cell is assembled into an outer package. After injecting the prepared electrolyte 100, the battery cell is packaged, allowed to stand, formed, shaped, and capacity tested, etc., to finally prepare implementation batteries 1 to implementation batteries 14 and comparison batteries 1 to comparison batteries 7.

[0090] The electrolyte 100 of Example 1 is applied to the implementation battery 1, the electrolyte 100 of Example 2 is applied to the implementation battery 2, the electrolyte 100 of Comparative Example 1 is applied to the comparative battery 1, and so on.

[0091] Table 1 below shows the composition parameters of the electrolyte 100 of Examples 1 to 14 and Comparative Examples 1 to 7.

[0092] Table 1: Composition parameters of the electrolyte 100 of Examples 1 to 14 and Comparative Examples 1 to 7.

[0093]

[0094] Among them, in Table 1, the structural formula of I-1 of the first additive is: The structural formula of the first additive Ⅰ-2 is: The structural formula of the first additive, Formula I-3, is:

[0095] In Example 12, the types of the second additive include DTD, PST and MMDS, and in the electrolyte 100, the mass fraction of the second additive is 1%, wherein the mass fraction of DTD is 0.5%, the mass fraction of PST is 0.2%, and the mass fraction of MMDS is 0.3%.

[0096] Performance test of battery 200:

[0097] 1. Cycling performance test of implementation battery 1 to implementation battery 14 and comparison battery 1 to comparison battery 7 at room temperature:

[0098] The above-mentioned implementation batteries 1 to implementation batteries 14 and comparison batteries 1 to comparison batteries 7 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 25°C, the cycle charge and discharge rate was 1C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 200), the charge and discharge voltage window was 2.5V to 3.65V (that is, the charge cut-off voltage of battery 200 is 3.65V, and the discharge cut-off voltage of battery 200 is 2.5V; it is generally believed that when the charge cut-off voltage is ≥4V, the charge cut-off voltage of battery 200 is higher), and the capacity retention rate after 500 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.

[0099] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 200 is first charged from 2.5V to 3.65V, and then discharged from 4.2V to 3.65V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.

[0100] It can be understood that the capacity retention rate of the battery 200 after 500 cycles at 25°C can characterize the cycle performance of the battery 200 under normal temperature conditions. The higher the capacity retention rate of the battery 200 after 500 cycles at 25°C, the better the cycle performance of the battery 200 under normal temperature conditions.

[0101] Table 2 shows the capacity retention rates of Example Batteries 1 to 14 and Comparative Batteries 1 to 7 after 500 cycles at 25° C.

[0102] 2. Cycling performance test of implementation battery 1 to implementation battery 14 and comparison battery 1 to comparison battery 7 in a high temperature environment:

[0103] The above-mentioned implementation batteries 1 to implementation batteries 14 and comparison batteries 1 to comparison batteries 7 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 45°C, the cycle charge and discharge rate was 1C, the charge and discharge voltage window was 2.5V to 3.65V, and the capacity retention rate after 500 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.

[0104] It can be understood that the capacity retention rate of the battery 200 after 500 cycles at 45°C can characterize the cycle performance of the battery 200 in a high temperature environment. The higher the capacity retention rate of the battery 200 after 500 cycles at 45°C, the better the cycle performance of the battery 200 in a high temperature environment.

[0105] Table 2 shows the capacity retention rates of Example Batteries 1 to 14 and Comparative Batteries 1 to 7 after 500 cycles at 45° C.

[0106] 3. Storage performance test of implementation battery 1 to implementation battery 14 and comparison battery 1 to comparison battery 7 at high temperature:

[0107] The implementation batteries 1 to 14 and the comparison batteries 1 to 7 were placed separately in a thermostat in sequence, the temperature of the thermostat was adjusted to 25°C, and the battery was allowed to stand for 10 minutes. The battery 200 was charged with a constant current at a charge and discharge rate of 0.5C until the voltage of the battery 200 was 3.65V, and then the battery 200 was charged with a constant voltage of 3.65V until the voltage of the battery 200 was cut off at 0.05C, and the battery was allowed to stand for 30 minutes, and the initial fully charged volume V0 of the electrode assembly 210 was tested; the temperature of the thermostat was adjusted to 60°C, and the battery was allowed to stand for 30 minutes. The battery 200 was charged with a constant current at a charge and discharge rate of 0.5C until the voltage of the battery 200 was 3.65V, and the battery was allowed to stand for 1 hour. After the above steps were repeated twice, the battery 200 was recharged, and the battery 200 was stored for 60 days. After the electrode assembly 210 was cooled, the fully charged volume V1 of the electrode assembly 210 was tested at this time; the volume expansion rate of the electrode assembly 210 stored at 60°C for 60 days = (V1 / V0)-1×100%.

[0108] It can be understood that the volume expansion rate of the battery 200 stored at 60°C for 60 days can characterize the storage performance of the battery 200 at high temperature. The smaller the volume expansion rate of the battery 200 stored at 60°C for 60 days, the better the storage performance of the battery 200 at high temperature.

[0109] Table 2 shows the values ​​of the volume expansion ratios of Example Batteries 1 to 14 and Comparative Batteries 1 to 7 after storage at 60° C. for 60 days.

[0110] Table 2 below shows the performance parameters of implementation batteries 1 to implementation batteries 14 and comparison batteries 1 to comparison batteries 7.

[0111] Table 2: Performance parameters of implementation batteries 1 to 14 and comparative batteries 1 to 7.

[0112]

[0113] Please refer to Table 1 and Table 2. From the data of Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that the electrolyte 100 of Examples 1 to 3 all include the first additive and the second additive, and the mass fraction a of the first additive, the mass fraction b of the second additive, and the value of a / b are all within a reasonable range, while the electrolyte 100 of Comparative Example 1 includes neither the first additive nor the second additive, and the electrolyte 100 of Comparative Examples 2 and 3 only include the first additive but not the second additive, and the mass fraction of the first additive in Comparative Example 2 is relatively small, and the mass fraction of the first additive in Comparative Example 3 is relatively large, which makes the electrolyte 100 of Example 1 to Example 3 at 25°C, 4 The capacity retention rate of 500 cycles at 5°C is higher than that of 500 cycles at 25°C and 45°C for comparison batteries 1 to 3, and the volume expansion rate of implementation battery 1 to implementation battery 3 stored at 60°C for 60 days is lower than that of comparison battery 1 to comparison battery 3 stored at 60°C for 60 days, which indicates that when the electrolyte 100 includes the first additive and the second additive, the first additive preferentially undergoes a reduction decomposition reaction compared to other components in the electrolyte 100 to generate aminosulfonate ions, and the aminosulfonate ions combine with lithium ions in the electrolyte 100 to form aminosulfonate lithium and adhere to the surface of the negative electrode plate 213 to form an SEI film. Lithium aminosulfonate has good electrical insulation and good lithium ion transmission performance, which can improve the chemical stability of the SEI film to reduce the consumption of lithium ions in the SEI film and repair process. In addition, the product of the reduction decomposition reaction of the first additive also includes free radicals containing conjugated groups. Such free radicals containing conjugated groups have strong nucleophilicity. The free radicals containing conjugated groups can effectively promote the ring opening of the second additive and make the second additive form a sulfur-containing substance with a higher degree of polymerization. The first additive and the second additive have a synergistic effect, so that the degree of polymerization of the polymer formed by the second additive is higher, thereby making the solubility of the SEI film in the electrolyte 100 lower, which is conducive to reducing the dissolution of the SEI film during high-temperature cycling, thereby slowing down the consumption of lithium ions in the electrolyte 100 under high-temperature cycling, and ultimately making the implementation battery 1 to the implementation battery 3 have good cycle performance in normal temperature environment and high temperature environment, and have higher high-temperature storage performance. When only the first additive is added to the electrolyte 100 without adding the second additive, the thermal stability of the electrolyte 100 can be improved, but the degree of improvement is not large.

[0114] It can be seen from the data of Examples 1 to 3 and 12 that, under the same other conditions, the second additive in Example 1 is DTD, the second additive in Example 2 is PST, the second additive in Example 3 is MMDS, and the second additive in Example 12 includes DTD, PST and MMDS. The capacity retention rates of Battery 1 to Battery 3 and Battery 12 after 500 cycles at 25°C and 500 cycles at 45°C are both high, as well as the volume expansion rate after storage at 60°C for 60 days. In other words, Battery 1 to Battery 3 and Battery 12 have good cycle performance in both normal temperature and high temperature environments, and have high high temperature storage performance. Among them, the implementation battery 12 has the best cycle performance under normal temperature environment and high temperature environment, and the best high temperature storage performance, which means that when the second additive is mixed with multiple cyclic sulfur-containing additives, and the proportions of the multiple cyclic sulfur-containing additives are controlled within a reasonable range, the second additive and the first additive have a better synergistic effect, so that the second additive can generate a polymer with a higher degree of polymerization, so that the SEI film has a higher solubility in the electrolyte 100, so that the electrolyte 100 of Example 1 has a higher thermal stability, so that the implementation battery 1 has better thermal stability and safety performance.

[0115] From the data of Example 1, Example 4 to Example 6, it can be seen that, under the same other conditions, the mass fraction b of the second additive in Example 1, Example 4 to Example 6 all satisfies the range of 0.05%≤b≤2%, and as the mass fraction of the second additive increases, the capacity retention of the corresponding battery 200 after 500 cycles at 25°C first increases and then decreases, the capacity retention after 500 cycles at 45°C first increases and then decreases, and the volume expansion after 60 days of storage at 60°C first decreases and then increases. This is because: in Example 1, the mass fraction of the second additive is neither too large nor too small, the first additive and the second additive have a good synergistic effect, the second additive generates a polymer with a higher degree of polymerization under the promotion of the first additive to form an SEI film attached to the surface of the negative electrode plate 213, and the SEI film is not easily dissolved by the electrolyte 100 under high-temperature cycles, the SEI film contains more sulfur, and the SEI film also has a higher thermal stability, so that the electrolyte 100 has a better thermal stability, so that the battery 1 has better cycle performance and high-temperature storage performance. In Example 4, the mass fraction of the second additive is too small. Even if the first additive can promote the ring opening of the second additive, the mass content of the second additive in the electrolyte 100 is still too small, so that the polymerization degree of the polymer formed by the first additive and the second additive is too low. The first additive and the second additive are combined, and it is difficult to form a complete SEI film on the surface of the negative electrode plate 213, which increases the impedance of the lithium ions in the battery 200 transmitted between the electrolyte 100 and the negative electrode plate 213, thereby reducing the cycle performance of the battery 200. In Examples 5 and 6, the mass fraction of the second additive is too large, and the polymerization degree of the polymer formed by the second additive is too high, so that the SEI film may be too thick, which increases the transmission path and impedance of the lithium ions in the battery 200 passing through the SEI film, thereby reducing the cycle performance of the battery 200.

[0116] From the data of Example 1, Example 13 and Example 14, it can be seen that, under the same other conditions, the structural formula of the first additive in Example 1 is The structural formula of the first additive of Example 13 is The structural formula of the first additive of Example 14 is The capacity retention rate of battery 1, battery 13 and battery 14 after 500 cycles at 25°C and 500 cycles at 45°C are both high, and the volume expansion rate after 60 days of storage at 60°C is high. In other words, battery 1, battery 13 and battery 14 have good cycle performance at room temperature and high temperature, and have high high temperature storage performance. Among them, battery 1 has the best cycle performance at room temperature and high temperature, and the best high temperature storage performance, which shows that: when the structural formula of the first additive is The first additive can better promote the ring opening of the second additive, so that the second additive can generate a polymer with a higher degree of polymerization. The first additive and the second additive have a better synergistic effect, so that the SEI film generated by the first additive and the second additive has better thermal stability, so that the electrolyte 100 of Example 1 has higher thermal stability, so that the battery 1 has better thermal stability and safety performance.

[0117] It can be seen from the data of Example 1, Example 7 and Example 8 that, under the same other conditions, the mass fraction a of the first additive in Example 1, Example 7 and Example 8 satisfies the range of 0.01%≤a≤1%, and the value of a / b satisfies the range of 0.1≤a / b≤1, and as the mass fraction of the first additive gradually increases, the corresponding capacity retention rate of the battery 200 for 500 cycles at 25°C and 500 cycles at 45°C first increase and then decrease, and the volume expansion at 60°C for 60 days first decreases and then increases, which shows that: when When the mass fraction of the first additive meets the reasonable range, and the value of a / b meets the reasonable range, the free radical containing the conjugated group formed by the decomposition of the first additive can effectively promote the ring opening of the second additive, so that the second additive forms a polymer with a high degree of polymerization on the surface of the negative electrode plate 213 and forms an SEI film. The SEI film with a high degree of polymerization is not easily dissolved by the electrolyte 100 under high temperature cycles, and the polymer formed by the second additive contains sulfur, so that the SEI film has good thermal stability, thereby making the electrolyte 100 have good thermal stability. On the other hand, the number of aminosulfonic acid ions formed by the decomposition of the first additive is also within a reasonable range, which can be combined with lithium ions in the electrolyte 100 and form an SEI film with electronic insulation and high ionic conductivity on the surface of the negative electrode plate 213, so as to form a film first, reduce the transmission impedance of lithium ions in the electrolyte 100, so that the battery 200 has good cycle performance when the electrolyte 100 is applied to the battery 200. Furthermore, the mass fraction of the second additive is not too large or too small to increase the internal resistance of the battery 200, so that the battery 1 has good high-temperature cycle performance and high-temperature storage performance. When the mass fraction of the first additive is too small, the mass proportion of the first additive in the electrolyte 100 is too small, so that the first additive cannot effectively play the role of promoting the ring opening of the second additive, the polymerization degree of the polymer formed by the second additive is low, and the sulfur content in the formed SEI film is reduced, so that the thermal stability of the SEI film is poor, and the thermal stability of the electrolyte 100 is poor, so that the cycle performance of the battery 7 is deviated. When the mass fraction of the first additive is too large, the free radicals containing conjugated groups decomposed by the first additive are too many, and only a small part of the free radicals containing conjugated groups are used to promote the ring-opening polymerization of the second additive. The remaining free radicals containing conjugated groups are free in the electrolyte 100, which will increase the impedance of the electrolyte 100, so that the cycle performance of the battery 8 is deviated.

[0118] It can be seen from the data of Examples 1, 9 to 11 that the electrolyte 100 of Examples 1, 9 and 11 all include a first additive and a second additive, and the sum of the mass fraction of the first additive and the mass fraction of the second additive is equal. By adjusting the mass fraction of the first additive and the mass fraction of the second additive respectively, the value of a / b can be adjusted. Among them, as the mass fraction of the first additive gradually increases, the mass fraction of the second additive gradually decreases, and the value of a / b gradually increases. The corresponding capacity retention rate of the battery 200 for 500 cycles at 25°C and 500 cycles at 45°C first increase and then decrease, and the volume expansion after storage at 60°C for 60 days first decreases and then increases. This shows that: when the value of a / b is within a reasonable range, the free radicals containing conjugated groups formed by the decomposition of the first additive can effectively promote the opening of the second additive, so that the second additive forms a polymer with a high degree of polymerization on the surface of the negative electrode plate 213 and forms an SEI film. The SEI film with a high degree of polymerization is not easily dissolved by the electrolyte 100 under high-temperature cycles, and the polymer formed by the second additive contains sulfur, so that the SEI film has good thermal stability, thereby making the electrolyte 100 have good thermal stability, so that the implementation battery 1 and the implementation battery 10 have good cycle performance. When the value of a / b is too large, the free radicals containing conjugated groups decomposed by the first additive are too many, and only a small part of the free radicals containing conjugated groups are used to promote the ring-opening polymerization of the second additive, and the remaining free radicals containing conjugated groups are free in the electrolyte 100, which will increase the impedance of the electrolyte 100, thereby reducing the cycle performance of the battery 200. In addition, the polymerization degree of the polymer formed by the first additive and the second additive is too low, and it is difficult for the first additive and the second additive to form a complete SEI film on the surface of the negative electrode plate 213, which increases the impedance of the lithium ions in the battery 200 transmitted between the electrolyte 100 and the negative electrode plate 213, thereby causing the cycle performance deviation of the battery 9. When the value of a / b is relatively small, even if the first additive can promote the ring opening of the second additive, the degree of polymerization of the polymer formed by the first additive and the second additive is still too low. When the electrolyte 100 is applied to the battery 200 and the battery 200 is in a high-temperature cycle, the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 213 is easily dissolved, thereby increasing the interfacial transmission impedance of lithium ions and consuming more lithium ions to repair the SEI film, resulting in poor high-temperature cycle performance and high-temperature storage performance of the implemented battery 11.

[0119] Comprehensively comparing Examples 1 to 14, Comparative Examples 2 and 3, when the mass fraction of the first additive and the mass fraction of the second additive are maintained within a reasonable range, the first additive and the second additive have a synergistic effect, and the protective effect on the electrode assembly 210 is better than the protection of a single additive under normal temperature and high temperature environments. This is because when the first additive and the second additive are used in a superimposed manner, the inorganic lithium salt generated by the first additive in the reduction process can be reduced in advance to cover the surface of the negative electrode plate 213, which can reduce the consumption of other additives in the formation process. At the same time, the free radicals containing conjugated groups generated by the reduction of the first additive can be combined with the second additive such as DTD, PST, MMDS, promote the ring-opening polymerization of the second additive to produce a product with a higher degree of polymerization, enhance the interface stability of the SEI film, reduce the consumption of additives during the charge and discharge cycle of the battery 200, and further improve the cycle performance of the battery 200. After the first additive and the second additive have reached the optimal content in improving the normal high temperature cycle, the improvement effect on the normal high temperature cycle gradually decreases with the increase in the amount of the first additive and the second additive added. This is because as the content of the first additive and the second additive increases, the active lithium consumed by the first additive and the second additive in the film formation process increases, which greatly reduces the content of active lithium in the battery 200, thereby reducing the discharge capacity of the battery 200, and then reducing the improvement of the first additive and the second additive on the normal high temperature performance.

[0120] In combination with Examples 1 to 14 and Comparative Examples 4 to 7, in Comparative Example 4, the mass fraction of the first additive and the mass fraction of the second additive are too small, so that the SEI film formed by the first additive and the second additive on the surface of the negative electrode plate 213 is incomplete, and thus the effect of improving the high temperature storage performance and high temperature cycle performance of the battery 200 is not obvious. In Comparative Example 7, the mass fraction of the first additive and the mass fraction of the second additive are too large. Although the first additive and the second additive can form an SEI film on the surface of the negative electrode plate 213, the first additive and the second additive will consume too many active lithium ions during the film formation process, so that the improvement effect on the cycle performance of the battery 200 is general. In the electrolyte 100 of Comparative Example 5, the value of a / b is too large, and in the electrolyte 100 of Comparative Example 6, the value of a / b is too small. When the ratio of the mass fraction of the first additive and the mass fraction of the second additive is not within a reasonable range, the interaction between the first additive and the second additive is weakened, so that the effect of improving the cycle performance of the battery 200 in a high temperature environment is not obvious. Therefore, the thermal stability of the electrolyte 100 can be adjusted by regulating the mass fraction of the first additive, the mass fraction of the second additive and the value of a / b, so that the battery 200 has good cycle performance both at room temperature and at high temperature, and the battery 200 has high high temperature storage performance and safety performance.

[0121] See also Figure 2 and Figure 3 The present application provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .

[0122] It can be understood that the battery 200 is electrically connected to the device body 310 .

[0123] In this embodiment, the electrolyte 100 includes a first additive and a second additive, and the first additive and the second additive cooperate with each other so that the SEI film formed on the surface of the negative electrode plate 213 has good thermal stability and good chemical stability, and finally the battery 200 has good cycle performance and safety performance in both normal temperature and high temperature environments, and has good high temperature storage performance. When the battery 200 is applied to the electrical device 300, in a high temperature environment, the battery 200 can provide stable power for the device body 310, which is conducive to improving the user experience.

[0124] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 2 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.

[0125] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.

[0126] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0127] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes: a first additive and a second additive, wherein the first additive is a sulfonamide additive and includes a cyclic conjugated group; and the second additive is a cyclic sulfur-containing additive.

2. The electrolyte according to claim 1, characterized in that The structural formula of the first additive is: Among them, R1 includes at least one of hydrogen, methyl, trifluoromethyl, and halogen, R2 is the cyclic conjugated group, and the cyclic conjugated group includes at least one of phenyl, pyridyl, pyrazinyl, thienyl, and pyrrolyl, R3 includes at least one of hydrogen, phenyl, methyl, and ethyl, and R4 includes at least one of hydrogen, phenyl, methyl, and ethyl.

3. The electrolyte according to claim 1, characterized in that The first additive is selected from and At least one of .

4. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction a of the first additive is in the range of 0.01%≤a≤1%.

5. The electrolyte according to claim 1, characterized in that The second additive is selected from at least one of vinyl sulfate, 1,3-propylene sultone and methylene methane disulfonate.

6. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction b of the second additive is in the range of 0.05%≤b≤2%.

7. The electrolyte according to any one of claims 1 to 6, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the electrolyte satisfies the relationship: 0.1≤a / b≤1.

8. The electrolyte according to claim 7, characterized in that The electrolyte satisfies the relationship: 0.5≤a / b≤1.

9. A battery, characterized in that: The battery comprises: An electrode assembly, the electrode assembly comprising a positive electrode sheet, a separator and a negative electrode sheet, the positive electrode sheet, the separator and the negative electrode sheet being stacked; and The electrolyte according to any one of claims 1 to 8, wherein the electrolyte is used to wet at least a portion of the electrode assembly.

10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.